2001
DOI: 10.1080/11250000109356398
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and tissue damage by heavy metal contamination in the German cockroach,Blattella germanica(Blattaria, Blattellidae)

Abstract: The accumulation of lead, cadmium, mercury, and chromium, supplied in the diet under experimental conditions, was studied in adult German cockroaches. Chronic heavy-metal exposure determined different rates of mortality, higher in males than in females. In both sexes, Hg, Pb, and Cr bioaccumulated in time, whereas Cd remained at constant low concentrations. Histological studies showed that in some organs and structures, such as the ovary, the testis, the alimentary canal and the fat bodies, there were profound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Additionally, numerous literature reports show that the bioamplification (biomagnification) of metals in organisms occurs at higher food chain levels [ 157 , 158 , 159 , 160 ]. The presence of heavy metals in insects and its impact on growth rate [ 161 , 162 , 163 ], mortality [ 164 , 165 , 166 , 167 , 168 ] and physiology [ 169 , 170 , 171 ] are well-known. Local adaptation of insects to environments contaminated with heavy metals was also reported [ 172 , 173 , 174 , 175 , 176 ].…”
Section: Effects Of Heavy Metals On Insects Including Aphidsmentioning
confidence: 99%
“…Additionally, numerous literature reports show that the bioamplification (biomagnification) of metals in organisms occurs at higher food chain levels [ 157 , 158 , 159 , 160 ]. The presence of heavy metals in insects and its impact on growth rate [ 161 , 162 , 163 ], mortality [ 164 , 165 , 166 , 167 , 168 ] and physiology [ 169 , 170 , 171 ] are well-known. Local adaptation of insects to environments contaminated with heavy metals was also reported [ 172 , 173 , 174 , 175 , 176 ].…”
Section: Effects Of Heavy Metals On Insects Including Aphidsmentioning
confidence: 99%
“…However, this process does not prevent damages of selected tissues. For example, Zhang et al (2001) showed that in cockroaches (Blattaria) contamination by different metals, including Pb, produces profound and irreversible pathological anomalies in the ovary, the testis, the alimentary canal, and the fat bodies. Isopods, diplopods (Crustacea), and collembola (Insecta) also showed ultrastructural alterations of midgut epithelium and midgut gland epithelium when exposed to different metals, including Pb (Köhler & Triebskorn, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…We found that most MGE candidates were specifically downregulated in specialists and encoded molecular functions involved in cell response, vesicular transport, organization of organelles and cytoskeleton, cilia assembly or cell adhesion (Table S4). Noticeably, these are the most frequent cell modifications observed in intestinal tissue damage by heavy metals from the diet (e.g., Bednarska et al, 2016;Köhler & Alberti, 1992;Zhang et al, 2001). Indeed, in soil ar- Our analysis also uncovered a number of upregulated MGE and MPS candidates associated with iron, copper and zinc binding and homeostasis, which can also be part of an adaptive mechanism of detoxification in specialist Dysdera.…”
Section: Genetic Changes Matching Phenotypic Convergence: Metal-indmentioning
confidence: 85%
“…We found that most MGE candidates were specifically downregulated in specialists and encoded molecular functions involved in cell response, vesicular transport, organization of organelles and cytoskeleton, cilia assembly or cell adhesion (Table ). Noticeably, these are the most frequent cell modifications observed in intestinal tissue damage by heavy metals from the diet (e.g., Bednarska et al, ; Köhler & Alberti, ; Zhang et al, ). Indeed, in soil arthropods subjected to heavy metal stress, midgut cells show evident histological modifications indicative of metal deposition in intracellular granules and gut epithelial degeneration.…”
Section: Discussionmentioning
confidence: 99%